Effective Ruby - Phippen, Sam; Safari eBooks ([Place of publication not identified] : Addison-Wesley, 2015)
"Each of the video's five lessons includes items centered on a key topic. The video starts with items focused on how to make effective use of arrays and hashes before moving on to lessons that teach viewers how to improve their objects by creating seams between them and how to write excellent tests for their Ruby applications. Next, the training teaches viewers how to solve problems associated with enumerables and callables, and finally how to best make use of the standard library. After watching this video, Rubyists will have gained the knowledge necessary to really master the language; viewers will be able to immediately apply the advice, tips, and tricks learned to the Ruby programs they're writing to improve the quality of their code."--Resource description page.
Title taken from title screen (Safari, viewed July 7, 2015).
Date of publication taken from title screen.
Presenter, Sam Phippen.
Keywords: Ruby (Computer program language); Electronic books